Rebaudioside A Enhances LDL Cholesterol Uptake in HepG2 Cells via Suppression of HMGCR Expression - Ajat, Mokrish (Tanjung Malim, 2021)
Rebaudioside A Enhances LDL Cholesterol Uptake in HepG2 Cells via Suppression of HMGCR Expression by Ajat, Mokrish